An Expanded Scientifically Grounded Article on Marketing - Toshpo‘latova , Bahora; Gafurova , Dilobar (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article provides an in-depth analysis of the concept of marketing, its role in the economy and stages of development. The main functions of marketing, strategic approaches, consumer behavior and the importance of digital marketing today are highlighted based on concrete evidence. Also, factors for increasing the effectiveness of marketing activities and modern trends are described in detail.